ChemInform Abstract: Generation of Complex Azabicycles and Carbobicycles from Two Simple Compounds in a Single Operation Through a Metal‐Free Six‐Step Domino Reaction. Issue 33 (27th July 2016) - Bock, Christina M.; Parameshwarappa, Gangajji; Boenisch, Simon; Neiss, Christian; Bauer, Walter; Hampel, Frank; Goerling, Andreas; Tsogoeva, Svetlana B.
Abstract: This unprecedented two‐component six‐step chemodivergent domino reaction provides a straightforward, sustainable and atom economical route to difficult‐to‐access complex bicyclic architectures whose ratios can be controlled by the applied electrophiles and catalysts.